Konsep dan Strategi Pembelajaran Membaca Al-Qur’an Pada Kelompok Perempuan Kelurahan Kutaraya Kecamatan Kayuagung Kabupaten Ogan Komering Ilir - Rohmadi, Rohmadi (Institut Agama Islam Negeri Bengkulu, 2020)
Abstrack. Based on observations that have been carried out during the regular attendance of UIN Raden Fatah Palembang for 40 days in Kutaraya Village, Kayuagung District, Ogan Komering Ilir District, many community activities are based on religion. One of these religious activities is the recitation activity which was followed by a group of women in the Kutaraya village. The implementation of this activity takes place at Al-Hikmah Mosque every Monday and Tuesday. Until now there are 22 housewives who become members of the study. The core of this activity is the implementation of Qur'an learning activities, where each individual is taught the science of reading the Qur'an. This is what later made us feel interested to study further. This research is motivated by the high enthusiasm of mothers to keep learning to read the Qur'an, so that the method of tahsin was chosen as an effort to help the process of Qur’an learning in this study group. This study uses a qualitative approach to data collection techniques, namely, direct communication and document study. The results of this study indicate that the tahsin method has proven to be effective in increasing the ability to study. Indicators that the program is effective can be seen in several ways namely; 1) Organizing good material; 2) Effective communication; 3) Mastery and enthusiasm for the subject matter.